TYROBP-positive endothelial cell-derived TWEAK as a promoter of osteosarcoma progression: insights from single-cell omics - Wei, Zhi-qiang; Ding, Sheng; Yang, Yan-cai (Frontiers in Oncology, 2023)
Background: Endothelial cells (ECs) play a vital role in promoting the progression of malignant cells, and they exhibit heterogeneity in their phenotypic characteristics. We aimed to explore the initiating cells of ECs in osteosarcoma (OS) and investigate their potential interaction with malignant cells. Method: We obtained scRNA-seq data from 6 OS patients, and datasets were batch-corrected to minimize variations among samples. Pseudotime analysis was performed to investigate the origin of differentiation of ECs. CellChat was employed to examine the potential communication between endothelial cells and malignant cells, and gene regulatory network analysis was performed to identify transcription factor activity changes during the conversion process. Importantly, we generated TYROBP-positive ECs in vitro and investigated its role in OS cell lines. Finally, we explored the prognosis of specific ECs cluster and their impact on the tumor microenvironment (TME) at the bulk transcriptome level. Results: The results showed that TYROBP-positive ECs may play a crucial role in initiating the differentiation of ECs. TYROBOP-positive endothelial cells (ECs) exhibited the strongest crosstalk with malignant cells, likely mediated by TWEAK, a multifunctional cytokine. TYROBP-positive ECs exhibited significant expression of TME-related genes, unique metabolic and immunological profiles. Importantly, OS patients with low enrichment of TYROBP-positive ECs had better prognoses and a lower risk of metastasis. Finally, vitro assays confirmed that TWEAK was significantly increased in ECs-conditioned medium (ECs-CM) when TYROBP was over-expressed in EC cells, and could promote the proliferation and migration of OS cells. Conclusion: We concluded that TYROBP-positive ECs may be the initiating cells and play a crucial role in the promotion of malignant cell progression. TYROBP-positive ECs have a unique metabolic and immunological profile and may interact with malignant cells through the secretion of TWEAK. Keywords: TWEAK, osteosarcoma, TYROBP, tumor microenvironment, prognosis, endothelial cells